Lynton Keith Caldwell : An Environmental Visionary and the National Environmental Policy Act - Wertz, Wendy Read (Book collections on Project MUSE., 2014)
This is the story of a visionary leader, Lynton Keith Caldwell, who in the early 1960s introduced the study of the environment and environmental policy at a time when such areas of expertise did not exist. For the next three decades, Caldwell played a leading role in establishing ethics-based environmental policy and administration as major areas of inquiry in the United States and around the world. Through his tireless global travels, writing, and lectures, and his work with the US Senate, the IUCN, UN, and UNESCO, Caldwell became recognized for his contributions to environmental ethics an.